Material Anomaly as Ecocide in Ginsberg’s “Ballade of Poisons” and Dickinson’s “Agents Orange, Yellow, and Red”: Epiphany in Ecological Precarity - Henrikus Joko Yulianto (Universitas Sanata Dharma, 2023)
Ecocide has been a classic anthropogenic phenomenon from time to time, It dated from the Industrial Revolution in the 18th century to the present post-industrial era of digital technology. This anthropogenic activity correlates with an overconsumption of material things such as fossil fuels and other earth minerals. Despite the merit, these subterranean minerals in fact contain toxic particles that have detrimental impacts on any life form and the physical environment. This study discusses Allen Ginsberg’s poem “Ballade of Poisons” and Adam Dickinson’s “Agents Orange, Yellow, and Red” as two poetic texts from different periods, the modern and contemporary ones. The purpose of the study is to highlight how these two poems polemicize the anthropogenic overuse of material and chemical products as ecocide that wreaks havoc on any life form. The study uses close reading method by examining ecological aspects in the poems and then contextualize these aspects within ecopoetic perspectives by referring to some notions such as material transcorporeality and its intrusion on human’s body. Poetry as one literary genre becomes an agent of social change and an ecological epiphany in this present posthuman precarity. Ginsberg’s “Ballade of Poisons” and Dickinson’s “Agents Orange, Yellow, and Red” then serve as an agent to actualize epiphany in this present ecological precarity. Their epiphanic poetics evokes one’s instantaneous awareness of the hazards of material overuse and of the insubstantial natures of these things through the human’s material objectification.